Sensitivity analysis of an optimal access road location in hillyforest area: a GIS approach - Ismail, Mohd Hasmadi; Taylor, John C. (Science Publications, 2008)
There are various models for establishing the efficient forest road allocation and evaluating optimum density of forest roads network for the transport of timber commodity. Most of them are based on the calculation of common timber transport costs and costs for forest roads. Today, forest road design from traditional method continues to be transformed by remote sensing technology and advancement of GIS. It is now possible for a forester to analyze many different road location alternatives over a large geographic area in a minimal amount of time. A computer programming using GIS, digital terrain data and sensitivity analysis for locating optimal forest road access in a hill area is presented. The optimal access road location specifies destination (starting point) and target (ending point) of the desired path. These paths were allocated by calculated each individual criteria by given weights placed on each cell. Therefore, the objective of this work is to describe an attempt to compute the optimal allocation of forest road corridor in hilly area of Peninsular Malaysia using GIS approach and sensitivity analysis to satisfy the result. Finally, the model minimizes total cost of construction and forest environmental impacts resulting from a specific access road. Sensitivity analysis should be explored further to understand the effects of uncertainty in derivation of model parameter on model outputs. It is concluded that the location of optimal access path were established in the area can reduce the cost and environmental impact to the forest ecosystem.